Using the Theory of Protracted Social Conflict and Structural Violence to Unravel the Tigray-Ethiopian War - Frederick Appiah Afriyie; Frank Boateng Asomani (The Journal of Intelligence, Conflict and Warfare, 2025)
Ethiopia, Africa's oldest independent nation and a key player in the Horn of Africa’s security, has undergone significant political and economic transformations. Despite emerging as a regional powerhouse, Ethiopia faces a complex ethnic landscape with diverse demographic groups. The historically influential Tigray region, plunged into a civil conflict in November 2020, and involved ethno-regional militias, the federal government, and Eritrean forces. This conflict stems from historical tensions, including the autocratic rule of Meles Zenawi and the dominance of the Tigray People’s Liberation Front (TPLF). Prime Minister Abiy Ahmed Ali, who heralded for fostering unity, took office in 2018 but faced escalating ethnic tensions. Postponed elections and federal interventions fueled discontent, leading to the outbreak of the Tigray War in November 2020. Abiy's military offensive, initially portrayed as a targeted operation, escalated into a brutal conflict, drawing international concern. Accusations of civilian mistreatment and Eritrean involvement were initially denied but later acknowledged by the Ethiopian government. The Tigray War underscores the challenges of achieving ethnic harmony and political stability in Ethiopia. This paper analyzes the Tigray War in Ethiopia, tracing its origins from the 19th century to the present, examining its consequences. The article specifically employs the Protracted Social Conflict and Structural Violence Theories to explain the conflict.